2019
DOI: 10.1101/522151
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SHARQnet - Sophisticated Harmonic Artifact Reduction in Quantitative Susceptibility Mapping using a Deep Convolutional Neural Network

Abstract: Quantitative susceptibility mapping (QSM) reveals pathological changes in widespread diseases such as Parkinson's disease, Multiple Sclerosis, or hepatic iron overload. QSM requires multiple processing steps after the acquisition of magnetic resonance imaging (MRI) phase measurements such as unwrapping, background field removal and the solution of an ill-posed field-to-source-inversion. Current techniques utilize iterative optimization procedures to solve the inversion and background field correction, which ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Deep learning-based techniques can offer an increase in robustness and speed-up in computation. For example, SHARQnet 69 was designed for background field removal using a 3D convolutional neural network and was trained on synthetic background fields overlaid on top of a brain simulation. When the performance was compared with SHARP, RESHARP and V-SHARP, SHARQnet delivered accurate background field corrections on simulations and on in vivo data.…”
Section: Background Field Removalmentioning
confidence: 99%
“…Deep learning-based techniques can offer an increase in robustness and speed-up in computation. For example, SHARQnet 69 was designed for background field removal using a 3D convolutional neural network and was trained on synthetic background fields overlaid on top of a brain simulation. When the performance was compared with SHARP, RESHARP and V-SHARP, SHARQnet delivered accurate background field corrections on simulations and on in vivo data.…”
Section: Background Field Removalmentioning
confidence: 99%
“…Recently, several studies 44,47,48 for DL have suggested using simulated data as an alternative to in vivo data for training, which allows us to generate ground-truth information without the need of multiple scans. In addition, a similar non-DL approach (ie, machine learning-based algorithms) using simulated training data termed dictionary-based conductivity mapping 63 has previously been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, deep learning (DL) approaches have been introduced for various image reconstruction problems in MR. [37][38][39][40][41][42][43][44][45][46][47] Furthermore, it has recently been suggested to use DL for conductivity reconstructions as an alternative to the computation of the spatial derivatives. [48][49][50] These approaches describe the foundation of alternative algorithms, which allow solving the conductivity reconstruction problem.…”
Section: Introductionmentioning
confidence: 99%
“…Although many previous deep neural networks [55][56][57][58][59][60][61][62] We also compared DCRNet with one previous deep learning-based MRI phase reconstruction method (Phase-Unet). It was found that the phase wraps in the reconstructed images were disrupted by Phase-Unet, making it problematic for the phase unwrapping process of the QSM pipeline.…”
Section: Discussionmentioning
confidence: 99%